Assessment of port environmental protection in Taiwan. Issue 2 (23rd November 2020) - Tseng, Po-Hsing; Ng, ManWo
Abstract : Purpose: There are many different pollution reduction strategies even within different ports in the same country. Every port can learn from these environmental protection strategies. What remains universally key, though, is to select the optimum strategy to reduce pollution. This paper aims to use a fuzzy analytic hierarchy process (FAHP) to prioritize the relative weights of key criteria assessing the port environmental protection and select the best port in Taiwan. Design/methodology/approach: Four criteria and eleven sub-criteria of the FAHP model are developed through expert interviews and relevant literature review. Three alternative ports considered are Kaohsiung, Keelung and Taichung. The expert questionnaire samples (23) include four groups: shipping operators, port operators, governmental officials and academics. Findings: Results indicate that finance is the most important evaluation criteria, followed by port environmental policy, technology and stakeholders. Among the three ports compared, Kaohsiung Port is selected as the best port, followed by Keelung and Taichung port. Originality/value: The result of this paper can help fill the gap in the existing literature regarding decision analysis techniques for port pollution regulation and expect to present a holistic picture of the important evaluation criteria related to port environmental protection as well as raise issues of public awareness concern and consequently improve green port sustainability.